Evaluasi Tingkat Keterpakaian Koleksi Perpustakaan di Dinas Perpustakaan dan Kearsipan Kota Padang Panjang - Urrahmah, Aulia; Nelisa, Malta (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis paper discusses the evaluation of the level of use of library collections in the Padang Panjang Library and Archives Service. The purpose of using this paper is: (1) to describe the compatibility of the use of collections in the Padang Panjang Municipal Library and Archives Service; (2) describe the frequency of use of the library collection; (3) describes the number of collections used by the library.The research method used in testing this final paper is descriptive method. Data collection is done through a process of observation and interviews.The discussion in this paper is calculated from January 2018 to June 2019. The first indicator is to describe the intensity of the use of collections. The number of collections described as a comparison for collections used. The number of collections purchased was 5,257 copies or 27.38% of the 19,197 collections available. And for unused collections, 13,940 copies or 72.62% of the total collection. Based on the number of uses of the collection, only Â¼ collections are used and used by users. The second indicator is the frequency of use of collections which are described based on frequency graphs per class. The results of using the graph can be seen the level of usage of the collection per month. For the class with the most collections, the class is 800 with 2,246 copies and the lowest class is 700 with 97 copies. The last indicator is the number of collections used based on the criteria of the year published and the name of the publisher. For the year published from 2015 to 2018 the number of collections used was 1,270 while the publisher's name was approved 5,246 copies. Both of these criteria also oppose the level of use of collections in libraries because these collections are more often used and known by users.Â Keywords: Usability, collection, amount.